Paclobutrazol improves salt tolerance in quinoa: Beyond the stomatal and biochemical interventions. (29th May 2017) - Waqas, M.; Yaning, C.; Iqbal, H.; Shareef, M.; Rehman, H.; Yang, Y.
Abstract: Quinoa is gaining importance on global scale due to its excellent nutritious profile and environmental stress‐enduring potential. Its production decreases under high salt stress but can be improved with paclobutrazol application. This study showed involvement of some potential protective mechanisms in root and leaf tissues of quinoa plants treated with paclobutrazol (PBZ) against high salinity. The treatment levels were based on preliminary experiments, and it was found that salt stress (400 mm NaCl) markedly reduced growth and photosynthetic pigments while PBZ (20 mg/L) application significantly improved these attributes. Stomata density and aperture declined on adaxial and abaxial surfaces of leaves due to salinity. Paclobutrazol application significantly improved the stomatal density on both surfaces of leaves. Concentration of proline and soluble sugars increased in root and leaf tissues under salinity, which was more obvious in PBZ‐treated plants. Salinity stress induced the oxidative damage by increasing lipid peroxidation (MDA) level in roots and more specifically in leaf tissues. However, PBZ treatments ameliorated the drastic effects of salinity and markedly reduced oxidative damage in salt‐stressed quinoa plants. Enhanced activity of enzymatic antioxidants such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) was triggered by PBZ application, more pronounced in leaf than root tissues. Based on these findings, we conclude that PBZ application improves the salt tolerance in quinoa by activation of the above‐mentioned physiological and biochemical mechanisms specifically in leaves.